Axonal Transport and Neurodegeneration: How Marine Drugs Can Be Used for the Development of Therapeutics - Joseph A. White; Rupkatha Banerjee; Shermali Gunawardena (Marine Drugs, 2016)
Unlike virtually any other cells in the human body, neurons are tasked with the unique problem of transporting important factors from sites of synthesis at the cell bodies, across enormous distances, along narrow-caliber projections, to distally located nerve terminals in order to maintain cell viability. As a result, axonal transport is a highly regulated process whereby necessary cargoes of all types are packaged and shipped from one end of the neuron to the other. Interruptions in this finely tuned transport have been linked to many neurodegenerative disorders including Alzheimer’s (AD), Huntington’s disease (HD), and amyotrophic lateral sclerosis (ALS) suggesting that this pathway is likely perturbed early in disease progression. Therefore, developing therapeutics targeted at modifying transport defects could potentially avert disease progression. In this review, we examine a variety of potential compounds identified from marine aquatic species that affect the axonal transport pathway. These compounds have been shown to function in microtubule (MT) assembly and maintenance, motor protein control, and in the regulation of protein degradation pathways, such as the autophagy-lysosome processes, which are defective in many degenerative diseases. Therefore, marine compounds have great potential in developing effective treatment strategies aimed at early defects which, over time, will restore transport and prevent cell death.